2005
DOI: 10.1029/2003tc001621
|View full text |Cite
|
Sign up to set email alerts
|

Implications of volcanism in coastal California for the Neogene deformation history of western North America

Abstract: The geologic record of coastal California includes evidence of numerous volcanic centers younger than 30 Ma that do not appear to have erupted in an arc setting. By correlating these volcanic centers with specific slab windows predicted from analysis of magnetic anomalies on the Pacific plate, we add new constraints to tectonic reconstructions since 30 Ma. Our correlations, such as erupting the Morro Rock–Islay Hill complex south of the Pioneer fracture zone and the Iversen Basalt south of the Mendocino fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 96 publications
2
116
0
Order By: Relevance
“…Geological evidence (e.g. Wilson et al 2005), in agreement with thermo-mechanical and kinematic modelling (Nicholson et al 1994), show that the main strand of the brittle fault system jumped inland in several discrete steps to its current position, the San Andreas fault. These jumps were associated with inland diffusion of the ductile roots of the deformation system, probably triggered by lower crustal and upper mantle temperature diffusion, or controlled by integrated lithospheric strength variations (Popov 2009).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Geological evidence (e.g. Wilson et al 2005), in agreement with thermo-mechanical and kinematic modelling (Nicholson et al 1994), show that the main strand of the brittle fault system jumped inland in several discrete steps to its current position, the San Andreas fault. These jumps were associated with inland diffusion of the ductile roots of the deformation system, probably triggered by lower crustal and upper mantle temperature diffusion, or controlled by integrated lithospheric strength variations (Popov 2009).…”
mentioning
confidence: 77%
“…Hosgri fault, see Wilson et al 2005) (ii) the role of the Montery Microplate, believed to be partially subducted beneath continental North America and believed to influence the developmemt of the transform margin as well as its present state (e.g. McCrory et al 2009;Popov 2009) (iii) the coast effect, a term used to describe the effect of the high-conductance ocean body on the MT responses measured far inland The main objective of this paper is to review the MT results from the SAF in combination with other geophysical, geological and geochemical data and models in order to address fluid-related processes and their potential implications on the geodynamic setting, active tectonic processes and the mechanical state of the fault.…”
mentioning
confidence: 99%
“…Asthenospheric upwelling associated with this slab removal presumably gave rise to increased heat flow, partial melt, and the observed volcanism. Subsequent events in the Mojave Desert include reestablishment of subduction west of the Mojave Desert region, followed by slab removal again in the wake of the subducted Mendocino fracture zone and associated volcanism (Wilson et al, 2005). Thus, at least two episodes of Cenozoic volcanism and inferred asthenospheric upwelling occurred in the Mojave Desert region; either or both may have contributed to the observed low upper-mantle velocities in this region.…”
Section: Appendix Cmentioning
confidence: 99%
“…Furthermore, we assumed that the subducted slab does not form a slab window; as Erkan and Blackwell [2008] suggested, formation of large-scale slab windows is incompatible with the very low postsubduction heat flow regime of the GV and western SN regions. Nevertheless, partial slab windows may have formed as suggested by Wilson et al [2005], but the previous 1-D modeling showed that these differences have no significant effect for cases of deep slab/window locations [also see Van Wijk et al, 2001].…”
Section: Two-dimensional Thermal Modelmentioning
confidence: 99%